Penerapan Perilaku Kelompok yang Dimiliki Guru Mulok dalam Meningkatkan Komunitas Belajar di Kota Bukittinggi - Hendri; Junaidi; Supriadi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
The Ministry of Education and Culture encourages education units and educators to learn and share with each other through a learning community supported by the Merdeka Teaching Platform (PMM). In implementing the independent curriculum, teachers need new competencies and understanding in implementing this curriculum. It is necessary to have a community or groups consisting of educators to exchange inspiration and ideas in learning. This research aims to analyse the application of group behaviour in improving learning communities in Bukittinggi City. The method used in this research is qualitative with a descriptive approach. The results showed that the learning community as one of the competency improvement strategies for educators, in its implementation was carried out in a scheduled and unscheduled manner. Activities in learning communities are carried out by identifying learning needs or problems being faced, sharing problems and developing processes to find solutions. Learning communities provide a space for educators to communicate and share information, contextual issues, personal experiences that can build understanding and insight related to learning. After the implementation of learning community activities, there is still a need for regular feedback and evaluation of the learning community.